Preparation method of heteroatom doped starch-based porous carbon electrode material
Through the preparation method of heteroatom-doped starch-based porous carbon electrode material, the problem of insufficient performance of existing carbon material electrodes in supercapacitors is solved, and higher electrochemical energy storage performance and feasibility of industrial production are achieved.
Patent Information
- Application Number
- CN202411844767.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing carbon material electrodes have problems such as long internal ion diffusion paths, low electronic conductivity and high ion resistance in supercapacitors, which are difficult to meet the high performance needs of supercapacitors.
Through the preparation method of heteroatom-doped starch-based porous carbon electrode material, the carbon electrode material with excellent electrochemical properties is prepared by melt blending using N-methylmorpholine-N-oxide aqueous solution, starch and dopant, followed by pre-carbonization and high-temperature activated carbonization to obtain a carbon electrode material with excellent electrochemical properties.
This method can significantly improve the specific surface area utilization of carbon electrode materials, improve the material surface wettability and enhance the pseudocapacitance effect, and achieve higher electrochemical energy storage performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrode materials for supercapacitors, and in particular relates to a method for preparing a heteroatom-doped starch-based porous carbon electrode material. Background Art
[0002] Supercapacitors are one of the most promising energy storage devices, so the selection and preparation of their electrode materials often need to consider factors such as practicality, low cost and environmental friendliness. For this reason, among the many types of electrode materials that have been developed today, carbon materials, especially biomass carbon materials, stand out and attract widespread attention due to their low price, high specific surface area, good chemical stability, good conductivity, and wide working range. The naturally occurring non-graphite carbon hierarchical structure of biomass materials makes it unique, but typical preparation methods cannot control the morphology, porosity and surface chemical properties of the resulting materials. The porous carbon electrodes produced may have long internal ion diffusion paths, low electronic conductivity and relatively high ionic resistance.
[0003] In recent years, researchers have conducted many further studies on the optimization of preparation processes. In order to have a more precise control over the physical structure and surface chemical properties of the generated carbon materials, one is to introduce heteroatoms such as nitrogen, boron, sulfur and phosphorus through hydrothermal method, template method, etc. to induce more surface electrochemically active reaction sites, thereby greatly improving the utilization rate of the specific surface area of carbon-based materials while improving the surface wettability of the material and increasing the pseudocapacitive effect. The second is to enrich the pore structure of the material through activation method, carbonization method, etc. Appropriate pore structure, pore gap and distribution can promote the diffusion of ions. In actual experiments, in order to maximize the specific surface area and electrochemical properties of carbon materials, it is usually necessary to combine multiple preparation methods to obtain the final biomass carbon electrode material, such as hydrothermal method combined with activation method, template method combined with carbonization method, etc. However, commonly used preparation methods such as hydrothermal method and template method are not conducive to large-scale production. In order to achieve the popularization of supercapacitors and meet the needs of commercial production, it is urgent to find a new preparation method for the preparation of carbon electrode materials. Summary of the invention
[0004] The object of the present invention is to provide a method for heteroatom doping starch-based porous carbon electrode material.
[0005] The technical solution to achieve the purpose of the present invention is: a method for preparing a heteroatom-doped starch-based porous carbon electrode material, comprising the following steps:
[0006] Step 1, preparing an N-methylmorpholine-N-oxide aqueous solution having an N-methylmorpholine-N-oxide content of ≥ 75% by distillation under reduced pressure;
[0007] Step 2, starch, N-methylmorpholine-N-oxide aqueous solution and dopant are mixed in a certain mass ratio and heated to dissolve;
[0008] Step 3, the dissolved mixture is melt-blended and extruded through a twin-screw extruder to obtain mixed pellets;
[0009] Step 4, using a tubular furnace to pre-carbonize the mixed pellets under nitrogen atmosphere to obtain pre-carbonized carbon;
[0010] Step 5: Grind the pre-carbonized carbon into powder, mix it evenly with the activator aqueous solution, evaporate and carbonize the mixture at high temperature in a tubular furnace, cool the activated carbonized product to room temperature, pickle it with dilute hydrochloric acid, wash it with water until it is neutral, and dry it to obtain the final heteroatom-doped starch-based porous carbon electrode material.
[0011] In the second step of the method for preparing heteroatom-doped starch-based porous carbon electrode materials of the present invention, the dopant may be one or more of soybean powder, urea, melamine and ammonium polyphosphate.
[0012] In the second step of the preparation method of heteroatom-doped starch-based porous carbon electrode material of the present invention, the amount of N-methylmorpholine-N-oxide aqueous solution is 25% to 40%, the amount of starch is 35% to 60%, and the amount of dopant is 5% to 30%.
[0013] In step 3 of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the melt blending temperature is ≤130°C.
[0014] In the fourth step of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the pre-carbonization temperature is 400-600°C.
[0015] In the fifth step of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the high-temperature activation carbonization temperature is 600-800°C.
[0016] In the fifth step of the method for preparing the heteroatom-doped starch-based porous carbon electrode material of the present invention, the activator used is potassium hydroxide, and the mass ratio of alkali to carbon is (2-4):1.
[0017] Compared with the prior art, the advantages of the present invention are as follows: (1) the starch used in the present invention is a biomass carbon source, the output of which is second only to cellulose, and it has the advantages of being renewable, abundant in source, and low in cost, and it can be converted into a carbon material with a rich pore structure through pyrolysis, carbonization, etc.; (2) the present invention melt-mixes the N-methylmorpholine-N-oxide solvent containing heteroatoms and the dopant with starch through extrusion blending to achieve doping, thereby achieving the purpose of improving the electrochemical energy storage performance of the carbonized material. The method is simple and easy to implement industrially. DETAILED DESCRIPTION
[0018] The method for preparing the heteroatom-doped starch-based porous carbon electrode material of the present invention comprises the following steps:
[0019] Step 1, preparing an N-methylmorpholine-N-oxide aqueous solution having an N-methylmorpholine-N-oxide content of ≥ 75% by distillation under reduced pressure;
[0020] Step 2, starch, N-methylmorpholine-N-oxide aqueous solution and dopant are mixed in a certain mass ratio and heated to dissolve;
[0021] Step 3, the dissolved mixture is melt-blended and extruded through a twin-screw extruder to obtain mixed pellets;
[0022] Step 4, using a tubular furnace to pre-carbonize the mixed pellets under nitrogen atmosphere to obtain pre-carbonized carbon;
[0023] Step 5: Grind the pre-carbonized carbon into powder, mix it evenly with the activator aqueous solution, evaporate and carbonize the mixture at high temperature in a tubular furnace, cool the activated carbonized product to room temperature, pickle it with dilute hydrochloric acid, wash it with water until it is neutral, and dry it to obtain the final heteroatom-doped starch-based porous carbon electrode material.
[0024] In the second step of the method for preparing heteroatom-doped starch-based porous carbon electrode materials of the present invention, the dopant may be one or more of soybean powder, urea, melamine and ammonium polyphosphate.
[0025] In the second step of the preparation method of heteroatom-doped starch-based porous carbon electrode material of the present invention, the amount of N-methylmorpholine N-oxide aqueous solution is 25% to 40%, the amount of starch is 35% to 60%, and the amount of dopant is 5% to 30%.
[0026] In step 3 of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the melt blending temperature is ≤130°C.
[0027] In the fourth step of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the pre-carbonization temperature is 400-600°C.
[0028] In the fifth step of the method for preparing heteroatom-doped starch-based porous carbon electrode material of the present invention, the high-temperature activation carbonization temperature is 600-800°C.
[0029] In the fifth step of the method for preparing the heteroatom-doped starch-based porous carbon electrode material of the present invention, the activator used is potassium hydroxide, and the mass ratio of alkali to carbon is (2-4):1.
[0030] The standard three-electrode test system was used for the electrochemical performance test (including constant current charge and discharge test and cyclic charge and discharge test). A mixed slurry was obtained in an appropriate amount of anhydrous ethanol in the ratio of prepared carbon material: acetylene black (conductive agent): polytetrafluoroethylene (binder) = 8:1:1, and then evenly coated on the cleaned nickel foam collector. The dried nickel foam was kept at a pressure of 10MPa for 1min by a tablet press to obtain a working electrode. Hg / HgO reference electrode, platinum counter electrode, 6mol·L -1 The three-electrode system was composed of KOH solution electrolyte, and the electrochemical test was carried out using an AUTO electrochemical workstation (Metrohm PGSTAT302N, Switzerland).
[0031] Example 1
[0032] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 50 g of food-grade corn starch and 20 g of soybean powder at 100° C. The mixed materials were melt-blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. After cooling by an air-cooled conveyor, the materials were pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0033] The pretreated starch-based material was placed in a tube furnace and heated at 5 °C min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The heteroatom-doped starch-based porous carbon electrode material of the present invention was obtained by pickling with dilute hydrochloric acid, then washing with a large amount of deionized water until neutral, and drying. -1 The mass specific capacitance is 224.1F·g -1 .
[0034] Example 2
[0035] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 60 g of food-grade corn starch and 10 g of melamine at 100° C. The mixed materials were melt-blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. The materials were then cooled by an air-cooled conveyor and pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0036] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The heteroatom-doped starch-based porous carbon electrode material of the present invention was obtained by pickling with dilute hydrochloric acid, then washing with a large amount of deionized water until neutral, and drying. The current density was 1 Ag. -1 When the mass specific capacitance is 158.2F·g -1 .
[0037] Example 3
[0038] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 60 g of food-grade corn starch and 10 g of ammonium polyphosphate at 100° C. The mixed materials were melt-blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. After cooling by an air-cooled conveyor, the materials were pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0039] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The heteroatom-doped starch-based porous carbon electrode material of the present invention was obtained by pickling with dilute hydrochloric acid, then washing with a large amount of deionized water until neutral, and drying. The current density was 1A.g -1 When the mass specific capacitance is 258.9F·g -1 .
[0040] Example 4
[0041] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 50 g of food-grade corn starch, 10 g of soybean powder and 10 g of ammonium polyphosphate at 100° C. The mixed materials were melt blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. After cooling by an air-cooled conveyor, the materials were pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0042] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The heteroatom-doped starch-based porous carbon electrode material of the present invention was obtained by pickling with dilute hydrochloric acid, then washing with a large amount of deionized water until neutral, and drying. The current density was 1A·g -1 When the mass specific capacitance is 195.9F·g -1 .
[0043] Example 5
[0044] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 50 g of food-grade corn starch, 10 g of melamine and 10 g of ammonium polyphosphate at 100° C. The mixed materials were melt blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. After cooling by an air-cooled conveyor, the materials were pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0045] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The heteroatom-doped starch-based porous carbon electrode material of the present invention was obtained by pickling with dilute hydrochloric acid, then washing with a large amount of deionized water until neutral, and drying. The current density was 1A·g -1 When the mass specific capacitance is 168.3F·g-1 .
[0046] Comparative Example 1
[0047] Untreated food-grade corn starch was placed in a tube furnace at N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The sample was washed with dilute hydrochloric acid, then washed with a large amount of deionized water until neutral, and dried to obtain the comparative starch-based porous carbon electrode material of the present invention, the current density of which was 1A·g -1 When the mass specific capacitance is 95.9F·g -1 .
[0048] Comparative Example 2
[0049] Weigh 30 grams of propylene glycol and 70 grams of food-grade corn starch and mix and dissolve them at 100°C. The mixed materials are melt-blended and extruded twice in a micro twin-screw extruder. The four-stage working temperatures of the extruder are set to 115°C, 120°C, 120°C and 120°C, respectively. After cooling with an air-cooled conveyor, the materials are pelletized with a micro pelletizer to obtain a pretreated starch-based material.
[0050] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The sample was washed with dilute hydrochloric acid, then washed with a large amount of deionized water until neutral, and dried to obtain the comparative starch-based porous carbon electrode material of the present invention, whose current density was 1A.g -1 When the mass specific capacitance is 125.5F·g -1 .
[0051] Comparative Example 3
[0052] 30 g of N-methylmorpholine-N-oxide hydrate containing 13.3% water was weighed and mixed with 70 g of food-grade corn starch at 100° C. The mixed materials were melt-blended and extruded twice in a micro twin-screw extruder, and the four-stage working temperatures of the extruder were set to 115° C., 120° C., 120° C. and 120° C., respectively. After cooling by an air-cooled conveyor, the materials were pelletized by a micro pelletizer to obtain a pretreated starch-based material.
[0053] The pretreated starch-based material was placed in a tube furnace under N 2 At 5℃·min -1 The pre-carbonized carbon was mixed with 3 times the mass of KOH in deionized water and immersed for 30 min. The mixture was evaporated at 100 °C while stirring. The evaporated mixture was transferred to a tube furnace and heated at 5 °C·min -1 The temperature was raised to 700℃ at a rate of 1 mol·L and kept at this temperature for 2 h. -1 The sample was washed with dilute hydrochloric acid, then washed with a large amount of deionized water until neutral, and dried to obtain the comparative starch-based porous carbon electrode material of the present invention, the current density of which was 1A·g -1 When the mass specific capacitance is 139.1F·g -1 .
Claims
1. A method for preparing a heteroatom-doped starch-based porous carbon electrode material, characterized in that: The following steps are involved: Step 1, preparing an N-methylmorpholine-N-oxide aqueous solution having an N-methylmorpholine-N-oxide content of ≥ 75% by distillation under reduced pressure; Step 2, starch, N-methylmorpholine-N-oxide aqueous solution and dopant are mixed in a certain mass ratio and heated to dissolve; Step 3, the dissolved mixture is melt-blended and extruded through a twin-screw extruder to obtain mixed pellets; Step 4, using a tubular furnace to pre-carbonize the mixed pellets under nitrogen atmosphere to obtain pre-carbonized carbon; Step 5: Grind the pre-carbonized carbon into powder, mix it evenly with the activator aqueous solution, evaporate and carbonize the mixture at high temperature in a tubular furnace, cool the activated carbonized product to room temperature, pickle it with dilute hydrochloric acid, wash it with water until it is neutral, and dry it to obtain the final heteroatom-doped starch-based porous carbon electrode material.
2. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to claim 1, characterized in that: In the second step, the doping agent is one or more of soybean powder, urea, melamine and ammonium polyphosphate.
3. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to claim 1 or 2, characterized in that: In the second step, the amount of N-methylmorpholine-N-oxide aqueous solution is 25% to 40%, the amount of starch is 35% to 60%, and the amount of doping agent is 5% to 30%.
4. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to any one of claims 1 to 3, characterized in that: In step 3, the melt blending temperature is ≤130°C.
5. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to any one of claims 1 to 4, characterized in that: In the fourth step, the pre-carbonization temperature is 400-600°C.
6. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to any one of claims 1 to 5, characterized in that: In step 5, the high temperature activation carbonization temperature is 600-800°C.
7. The method for preparing a heteroatom-doped starch-based porous carbon electrode material according to any one of claims 1 to 6, characterized in that: The activator used in step 5 is potassium hydroxide, and the mass ratio of alkali to carbon is 2 to 4:1.
Citation Information
Patent Citations
Preparation method of activated carbon advanced pore structure
CN106185929A
Preparation method and application of starch-based mesoporous carbon with high specific surface area
CN110395731A
Biomass thermoplastic material, product and preparation method thereof
CN116410522A
Biodegradable biomass thermoplastic blending composite material, product and preparation method of biodegradable biomass thermoplastic blending composite material
CN116478512A
Negative electrode material and preparation method and application thereof
CN117550587A
Cited By
Method for rapidly and controllably preparing three-dimensional porous carbon material derived from waste macromolecules at room temperature
CN120328554A
A method for room-temperature rapid controllable preparation of waste polymer derived three-dimensional porous carbon material
CN120328554B